In vitro optical quality assessment of a monofocal IOL sutured to an artificial iris - Mayer, Christian; Son, Hyeck Soo; Łabuz, Grzegorz; Yildirim, Timur Mert; Auffarth, Gerd U.; Khoramnia, Ramin (Journal of cataract and refractive surgery, 2020)
Purpose: To assess whether the combined implantation of a monofocal IOL and an artificial iris had an effect on the IOL's optical performance. - Setting: David J. Apple International Laboratory for Ocular Pathology, Heidelberg, Germany. - Design: In vitro laboratory study. - Methods: IOL optical quality was assessed using an OptiSpheric IOL Pro II to measure the IOL's modulation transfer function (MTF) at 3.0 mm pupil size and spatial frequency of 100 lp/mm. Three ASPIRA-aAY IOLs with different base powers, 10.0 diopter (D) (IOL A), 20.0 D (IOL B), and 30.0 D (IOL C) were measured before and after suturing the IOL to an ArtificialIris (AI). The degree of IOL decentration about the center of the AI was also evaluated. - Results: The mean MTF values prior to suturing were 0.57, 0.65, and 0.63 for IOLs A, B, and C, respectively. After suturing to the AI, the mean MTF values were 0.52, 0.54, and 0.55 for IOLs A, B, and C, respectively. The decentration values in vertical direction were 0.20 mm, 0.00 mm, and 0.02 mm for IOLs A, B, and C, respectively. In horizontal direction, the decentration values were 0.42 mm, 0.10 mm, and 0.03 mm for IOLs A, B, and C, respectively. - Conclusions: The MTF decreased slightly in all 3 IOLs after they were sutured to the AI. The small differences, however, should be clinically irrelevant. This laboratory assessment showed that suturing of the IOL to the AI can be performed in a reliable and reproducible manner without deteriorating optical quality.
Gesehen am 09.11.2020